Food security and livelihood of tribal people in Bangladesh: The role of microfinance - Rahman, Mohammad Ataur; Paul, Shukdeb; Saha, Jiban Krishna (Fundamental and Applied Agriculture, 2019)
Microfinance is being considered as one of the most effective tools of improv- ing the food security and the livelihood. The present study was conducted to analyze the loan profiles, the impact of credit on the livelihood and food security level of the tribal households. The primary data were collected from randomly selected sixty women beneficiaries through the interview schedule in Khagrachari district of Bangladesh. Tabular analysis along with a DFID livelihood framework was used for data analysis. To assess the calorie intake level, seven days consumption data were converted to per person per day calorie intake level. The study showed that the beneficiaries received required amount of loan for different purposes such as petty business, dairy, agribusiness, trading of handicraft, fishery, etc., and they invested their loan money in the productive activities mostly. The loan recovery rate was highly satisfactory. The study also discovered that the assets possession of the households improved after utilizing the loan. The calorie intake level of the sample household members indicated around two-third members were food unsecured. As microfinance showed a positive impact on livelihood; different financial institutions, NGOs, private companies and local and for- eign donor agencies should come forward to offer financial help to the tribal community to improve their livelihoods and food security.